Evaluation of the production characteristics of the Jamunapari goat and its adaptability to farm conditions in Bangladesh (Bangladesh Veterinarian, 2010)
The growth rate, milk yield, milk composition and reproductive efficiency ofJamunapari goats were studied under semi-intensive conditions. Animals were allowedto graze for 6-7 hours and concentrate (17% CP, 11 MJ/kg DM) at 400g/head/day wasoffered twice daily. No body measurement was different in male and female goats. Theudder was capacious but pendulous. Testis length, breadth and scrotal circumferencewere 17.3 ± 1.5, 11.5 ± 1.7 and 42.4 ± 2.0 cm, respectively. The mean body weight at birthand at 12 months was 1.6 and 21.4 kg, respectively. The average growth rates of male andfemale kids were 59.4 and 48.2g/day, respectively. The overall rate of weight gain washighest in second month and lowest in 11th month. Highest milk yield was in secondmonth and lowest in the fifth month after kidding. Lactation length was 135.4 ± 14.9 and143.9 ± 13.2 days for does suckling one and two kids, respectively. Milk intake to growthratio was 15.6 ± 0.2 and 12.5 ± 0.3 for the litter size of one and two, respectively. Highestmilk fat, lactose and solids not fat (SNF) were in the later stage of lactation, whereasprotein and minerals were similar throughout the lactation. The average age at firstoestrus, age at first pregnancy and age at first kidding were 354.8 ± 17.1, 395.4 ± 29.6 and548.6 ± 68.1 days, respectively. The average number of services per pregnancy was 1.4.The gestation length was 152.8 ± 17.6 days. The average body weight just after kiddingand placenta weight were 26.7 kg and 342.4g, respectively. The overall litter size was 1.8and 32.9, 58.2 and 8.9% of kidding produced single, twins and triplets, respectively. Sexratio was 53.3 male to 46.7% female. Average onset of post-partum oestrus was 51 andinterval from parturition to pregnancy 69.3 days. Production of Jamunapari goats wascomparable with that of the Bengal goats.(Bangl. vet. 2010. Vol. 27, No. 1, 26 – 35)DOI: 10.3329/bvet.v27i1.5912